Characterization of the microstructure of the compositionally complex alloy Al1Mo0.5Nb1Ta0.5Ti1Zr1. (August 2016) - Jensen, J.K.; Welk, B.A.; Williams, R.E.A.; Sosa, J.M.; Huber, D.E.; Senkov, O.N.; Viswanathan, G.B.; Fraser, H.L.
Abstract: Electron microscopy, X-ray energy dispersive spectroscopy, and tomographic reconstructions were used to characterize a high entropy alloy predominantly composed of refractory elements. The intragranular microstructure was found to consist of a periodic two phase mixture, where a disordered bcc phase is aligned orthogonally in an ordered B2 phase. The phases were found to exhibit continuous lattice registry and an orientation relationship given by < 100 > bcc //<100 >B2, {001} bcc //{001}B2 . X-ray energy dispersive spectroscopy was used to determine the compositions of the phases, and spectral images were used in the tomographic reconstruction of the alloy to reveal the morphology and the elemental partitioning between phases. Graphical abstract: